Integrated HIV and STIs response: Trends in syphilis incidence and uptake of oral pre-exposure prophylaxis in Zambia - Kutha Banda; Nicholus C. Sande; Chipwaila C. Chunga; Belia Longwe; Kayawe Nkumbwa; Madaliso Silondwa; Nsanzya Maambo; Japhet Michelo; Prudence Haimbe; Trevor Mwamba; Hilda Shakwelele; Sandra Chilengi-Sakala; et al. (Journal of Public Health in Africa)
Background: Pre-exposure prophylaxis (PrEP) for human immunodeficiency virus (HIV) was introduced in Zambia to prevent transmission, but it does not protect against sexually transmitted infections (STIs) such as syphilis. Globally, STIs have risen alongside PrEP rollout, posing significant public health concerns that require urgent attention and targeted intervention strategies.